Isonitriles as Stereoelectronic Chameleons: The Donor–Acceptor Dichotomy in Radical Additions - Gomes, Gabriel dos Passos; Loginova, Yulia; Vatsadze, Sergey Z; Alabugin, Igor V (Journal of the American Chemical Society, 2018)
Radical addition to isonitriles (isocyanides) starts and continues all the way to the transition state (TS) mostly as a simple addition to a polarized π-bond. Only after the TS has been passed, the spin density moves to the α-carbon to form the imidoyl radical, the hallmark intermediate of the 1,1-addition-mediated cascades. Addition of alkyl, aryl, heteroatom-substituted, and heteroatom-centered radicals reveals a number of electronic, supramolecular, and conformational effects potentially useful for the practical control of isonitrile-mediated radical cascade transformations. Addition of alkyl radicals reveals two stereoelectronic preferences. First, the radical attack aligns the incipient C···C bond with the aromatic π-system. Second, one of the C–H/C–C bonds at the radical carbon eclipses the isonitrile N–C bond. Combination of these stereoelectronic preferences with entropic penalty explains why the least exergonic reaction (addition of the t-Bu radical) is also the fastest. Heteroatomic radicals reveal further unusual trends. In particular, the Sn radical addition to the PhNC is much faster than addition of the other group IV radicals, despite forming the weakest bond. This combination of kinetic and thermodynamic properties is ideal for applications in control of radical reactivity via dynamic covalent chemistry and may be responsible for the historically broad utility of Sn radicals (“the tyranny of tin”). In addition to polarity and low steric hindrance, radical attack at the relatively strong π-bond of isonitriles is assisted by “chameleonic” supramolecular interactions of the radical center with both the isonitrile π*-system and lone pair. These interactions are yet another manifestation of supramolecular control of radical chemistry.